ChemInform Abstract: Functionalization of an sp3 C—H Bond via a Redox‐Neutral Domino Reaction: Diastereoselective Synthesis of Hexahydropyrrolo[2, 1‐b]oxazoles. Issue 28 (15th July 2014) - Rahman, Matiur; Bagdi, Avik Kumar; Mishra, Subhajit; Hajra, Alakananda
Abstract Pyrrolidinooxazolidines (III) are prepared by microwave‐assisted reaction of pyrrolidine (I) with 2 equiv.